Procalcitonin for detecting community-acquired bacterial pneumonia - Devi Gusmaiyanto; Finny Fitry Yani; Efrida Efrida; Rizanda Machmud (Indonesian Pediatric Society Publishing House, 2015)
Background Pneumonia is a major cause of morbidity and mortality in children under five years of age. Pneumonia can be of bacterial or viral origin. It is difficult to distinguish between these two agents based on clinical manifestations, as well as radiological and laboratory examinations. Furthermore, bacterial cultures take time to incubate and positive results may only be found in 10-30% of bacterial pneumonia cases. Procalcitonin has been used as a marker to distinguish etiologies, as bacterial infections tend to increase serum procalcitonin levels. Objective To determine the sensitivity, specificity, positive predictive value and negative predictive value of procalcitonin in community-acquired bacterial pneumonia. Method This cross-sectional study was conducted in the Pediatric Health Department of Dr. M. Djamil Hospital, Padang. Subjects were selected by consecutive sampling. Procalcitonin measurements and PCR screening were performed on blood specimens from 32 pneumonia patients and compared. Results Of the 32 subjects, most were boys (56.25%), under 5 years of age (99%), and had poor nutritional status (68.75%). Using a cut-off point of 0.25 ng/mL, procalcitonin level had a sensitivity of 92%, specificity 50%, positive predictive value 88%, and negative predictive value 60% for diagnosing bacterial pneumonia. Using a cut-off point of 0.5 ng/mL, procalcitonin level had a specificity of 46%, specificity 83%, positive predictive value 91%, and negative predictive value 25%. Conclusion A cut-off point of 0.25 ng/mL of procalcitonin level may be more useful to screen for bacterial pneumonia than a cutoff point of 0.5 ng / mL. However, if the 0.25 ng/mL cut-off point is used, careful monitoring will be required for negative results, as up to 40% may actually have bacterial pneumonia. [Paediatr Indones. 2015;55:65-9.].